İbn Khaldun’s Asabiyyah Theory and Its Present-day Provisions - Azimli, Elnur (Scholarya Demo Journal of Ruby, 2021)
Ibn Khaldun was a 14th-century Muslim thinker and scholar who lived in North Africa. He was the last bright star in the sky of Islamic thought and science at a time when Islamc culture began to pause, regress, and weaken. As a prominent politician, he spent his entire career battling for political power, gaining extensive experience in the field of management. Ibn Khaldun wrote books and developed concepts based on his wisdom, worldview, and experiences. One of these concepts, asabiyyah, which appears frequently in Ibn Khaldun’s book Muqaddimah, and its modern manifestations have been investigated in this study. Asabiyyah was a term used in Arab society since the Jahiliyyah (pre-Islamic era) to express a sense of protecting and caring for close relatives. By coining this term, Ibn Khaldun demonstrated the importance of asabiyyah in establishing a state, ruling it, and maintaining power. In the scope of our research, we attempted to apply Ibn Khaldun’s asabiyyah concept from history to modern societies and make it functional for today. As a result, we expressed that asabiyyah, whose ultimate goal is to gain power, in the form of political parties in modem nation-states. Unlike in medieval states, the governing group in today’s democratically ruled states relies on public vote and support to stay in power, and thus always strives to strengthen its asabiyyah among the people. In comparison to examples from Muqaddimah, our study demonstrates some factors that strengthen asabiyyah in modern states. Finally, we attempted to explain, using examples from Ibn Khaldun, how the ruling party annihilates people’s asabiyyah (group feeling) through repressions in oppressive regimes that are not governed democratically.